Human Resource Management: The Effect of Job Insecurity Management on Replacement Intentions through Alternative Work as a Moderator - Akbar, Nanda Hikmal; Gunawan, Asep; Febriyansyah, Hevy (Journal of Educational Management Research, 2025)
This study examines the phenomenon of turnover intention as a significant challenge in the creative industry sector, focusing on the role of job insecurity and the perception of alternative job opportunities in Indonesia. Using a quantitative approach and causal-explanatory design, this study involved 103 employees of CV Katen Creative Media, a creative startup in Cirebon, as respondents through saturated sampling techniques. Data were collected using a structured questionnaire and analyzed through Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4. The research findings indicate that job insecurity has a significant positive influence on relocation intentions, suggesting that the uncertainty of employment contracts and a lack of career clarity increase employees' desire to leave the organization. Further, the perception of alternative jobs also significantly influenced the intention to move, implying that the belief in the existence of better job opportunities outside drove the decision to quit. However, the role of moderation of the perception of alternative jobs on the relationship between job insecurity and intention to move is not statistically significant. These results underscore the complexity of intentional shift behaviors in the creative sector and highlight the importance of job security guarantees for employee retention and stability. The practical implications underscore the need for a human resource management strategy that prioritizes enhancing job security and providing transparent career paths. The implications of these findings enrich understanding of the dynamics of intent to move in the creative industry ecosystem in developing countries, providing an empirical foundation for the development of more effective employee retention models as well as direction for future research.